IGN and Development of an Interactive Learning Application Software to Enhance Alphabet Knowledge in Kindergarten Learners - G. Mancao, Shiela (The Future of Education Journal, 2025)
The study was conducted to design and develop an interactive alphabet learning application software and to find out its effectiveness in enhancing letter name and sound knowledge of kindergarten learners. To achieve this goal, this study utilized sequential developmental research design, adapting the ADDIE (Analysis, Design, Development, Implementation and Evaluation) instructional model to design and develop the interactive learning application. The development of the instructional material was anchored on Information Processing Theory, Bottom-up Theory, Constructivist Learning Theory and Cognitive Development Theory. Having five kindergarten learners as participants, this study also utilized quasi-experimental design to find out its effectiveness when used by kindergarten learners as a supplementary tool to develop and improve the alphabet knowledge. Based on the results, the least learned letters were Ii, Ee, Nn, Pp, Bb and Dd. These could be enhanced using technology tools such as the internet and smartphone which are both common among learners. Moreover, the Interactive Application Software was found out to be appropriate to address their needs. This study concluded that has significantly improved the alphabet knowledge of the kindergarten learners. Thus, it is recommended to be used as a supplementary and intervention tool in learning the letter names and sounds. Kindergarten teachers are also recommended to devise similar learning material which addresses least learned competencies brough about by distance learning. Finally, it is suggested that future studies be conducted to investigate the effectiveness of the same materials to another set of learners.